2018
DOI: 10.1111/psyp.13305
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow modulations during antisaccade preparation in chronic hypotension

Abstract: In addition to symptoms including fatigue, dizziness, reduced drive, or mood disturbance, individuals with chronic low blood pressure (hypotension) frequently report cognitive complaints. While attentional deficits have been empirically confirmed, it is still unknown whether the impairments also encompass executive functions. This study investigated cerebral blood flow modulations in hypotension during a precued antisaccade/prosaccade task requiring the executive function of proactive inhibition in addition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 115 publications
(216 reference statements)
0
3
0
Order By: Relevance
“…However, there is evidence challenging the dissociation between peripheral and cerebral hemodynamics [ 30 , 33 ]. For example, healthy subjects with chronically low blood pressure exhibited smaller increases in MCA blood flow velocities during cognitive activity than those with normal blood pressure [ 11 , 17 , 18 ]. Pharmacologically induced blood pressure enhancement led to increase of tonic MCA perfusion and stronger flow velocity responses during cognition [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence challenging the dissociation between peripheral and cerebral hemodynamics [ 30 , 33 ]. For example, healthy subjects with chronically low blood pressure exhibited smaller increases in MCA blood flow velocities during cognitive activity than those with normal blood pressure [ 11 , 17 , 18 ]. Pharmacologically induced blood pressure enhancement led to increase of tonic MCA perfusion and stronger flow velocity responses during cognition [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the role of the ‘central command’ during cognitive paradigms in fTCD studies has received very little attention in the human NVC literature [ 67 ]. Previous studies suggested that the preparatory process of blood flow adjustment involves alertness of attentional function [ 68 ], correlated with increasing CBF response before the onset of exercise that is likely governed by the ‘central command’ network [ 69 ]. Therefore, increased CBFV at the onset of all paradigms, independently of complexity or duration, was probably determined by the effects of ‘central command’ on the neurovascular unit.…”
Section: Discussionmentioning
confidence: 99%
“…BOLD) [ 10 , 78 , 79 ] and our paradigms. According to the ‘central command’ hypothesis, the lack of marked differences in CBFV responses with varying durations could be explained by the anticipatory response to cognitive demand in the attentional process [ 68 ], governing an upsurge of CBFV around 5s after onset stimulation, without further influence of the duration of stimulation on the NVC mechanism.…”
Section: Discussionmentioning
confidence: 99%